2019
DOI: 10.1183/13993003.00900-2019
|View full text |Cite
|
Sign up to set email alerts
|

ERS/EAACI statement on severe exacerbations in asthma in adults: facts, priorities and key research questions

Abstract: Despite the use of effective medications to control asthma, severe exacerbations in asthma are still a major health risk and require urgent action on the part of the patient and physician to prevent serious outcomes such as hospitalisation or death. Moreover, severe exacerbations are associated with substantial healthcare costs and psychological burden, including anxiety and fear for patients and their families. The European Academy of Allergy and Clinical Immunology (EAACI) and the European Respiratory Societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 225 publications
(245 reference statements)
1
45
0
Order By: Relevance
“…The prevention of exacerbations remains an important therapeutic target for patients with asthma [23]. In this study, we observed an 86.2% reduction from baseline in exacerbation rate after both 12 and 24 months of follow-up.…”
Section: Discussionsupporting
confidence: 52%
“…The prevention of exacerbations remains an important therapeutic target for patients with asthma [23]. In this study, we observed an 86.2% reduction from baseline in exacerbation rate after both 12 and 24 months of follow-up.…”
Section: Discussionsupporting
confidence: 52%
“…To date, there is very little information available on patients with asthma who have COVID‐19. In general, viruses, including rhinoviruses and respiratory syncytial viruses, have been shown to induce asthma episodes or exacerbations 118,119 . Mounting evidence implicates that particular viral pathogens, namely the human rhinovirus and respiratory syncytial virus, are among the most likely culprits in asthma inception 119 .…”
Section: Specific Considerations In the Management Of Different Allermentioning
confidence: 99%
“…In general, viruses, including rhinoviruses and respiratory syncytial viruses, have been shown to induce asthma episodes or exacerbations. 118,119 Mounting evidence implicates that particular viral pathogens, namely the human rhinovirus and respiratory syncytial virus, are among the most likely culprits in asthma inception. 119 Bacterial infections and colonization have also been associated with exacerbation and recurrent wheeze, an effect that may be independent, or a cofactor with viruses.…”
Section: Asthmamentioning
confidence: 99%
“…Among patients who end up at the ICU, the mortality rate is high [ 1 ]. While individuals with chronic respiratory diseases such as allergy, asthma and COPD are generally at risk of virally induced (severe) exacerbations [ 2 ], interestingly, these populations seemed under-represented among those with severe-COVID-19 disease in the initial reports from China [ 3 , 4 ]. However, more recent reports from the USA COVID-NET hospitals show chronic lung disease as an underlying condition in approximately 30% of hospitalized patients with COVID-19 [ 5 ], while especially those with COPD appeared at risk [ 6 ].…”
mentioning
confidence: 99%